Ultrastructural changes in the liver in experimental hyperhomocysteinemia on the background of hypo- and hyperthyroidism - V.M. Nechiporuk; Zoya M. Nebesna; О.V. Kovalchuk; L.O. Pentiuk; Mykhaylo M. Korda (Вісник медичних і біологічних досліджень, 2021)
Thyroid hormones play a crucial role in maintaining metabolic homeostasis throughout life. It is well known that the liver and thyroid gland are closely related, with thyroid hormones playing an important role in de novo lipogenesis, beta-oxidation of fatty acids, cholesterol metabolism and carbohydrate metabolism. High levels of circulating homocysteine ​​(HC) (hyperhomocysteinemia (HHC)) are an independent factor in the development of atherosclerosis, induce the completion of the cell cycle, accelerate the aging process, cause apoptosis in endothelial cells and neurons. The aim of the study – to establish the reorganization of the structural components of the liver under the conditions of simulated HHCy, hyper- and hypothyroidism and their combined effects. Materials and Methods. Thiolactone HHCy was simulated by administering to animals exogenous HC in the form of thiolactone at a dose of 100 mg/kg body weight once a day for 28 days. Hyperthyroidism was simulated by daily administration of L-thyroxine at a dose of 200 μg/kg on day 21, hypothyroidism – daily administration of mercazolyl at a dose of 10 mg/kg on day 21. Separate groups of animals were administered L-thyroxine and mercazolyl in parallel with HC. Results. It was found that under the conditions of simulated HHCy, hypo- and hyperthyroidism in the liver of experimental animals there are disorders of microcirculation, which at the submicroscopic level were manifested by sludge-phenomenon, stasis of blood cells in dilated lumens of sinusoids, damage of the endothelial cells ultrastructure, of some endoplasmic reticulum tubules, vacuoles and dilated cysterns of the Golgi complex, mitochondria were solitary with homogeneous, light matrix and lysed crystae, Disse spaces were mostly expanded, they had Kupffer cells, cytoplasm of sinusoid endothelial cells was enlightened, swollen and destructively changed, and the blood cells and vacuole-like structures were present in the lumen of sinusoids. Conclusions. Both HHCy and hypo- or hyperthyroidism separately and especially under the conditions of their synergistic action caused the presence of “light” and “dark” hepatocytes in the liver lobules, as a manifestation of adaptive-compensatory, destructive and development of necrotic changes in the body. Irreversible damage to the components of the nuclei and organelles of hepatocytes develops, which leads to disruption of synthetic, energetic and detoxification processes in cells and, consequently, in the organs